The Challenges of the Digital Divide in the Online Learning Process During the COVID-19 Pandemic in Indonesia - Ilham Gemiharto; H.E. Niluka Priyadarshani (Yayasan Ilomata, 2022)
The digital divide is one of the problems faced by the government since the COVID-19 pandemic occurred. All face-to-face activities in all development sectors are transferred online. The unpreparedness of communication technology infrastructure in Indonesia is one of the obstacles to online learning activities that require a stable internet connection, even in urban areas that already have communication infrastructure with 5G networks. However, it turns out that the problem is not only with infrastructure, what is more important than that is the opportunity and ability of the community to use communication technology. In this study, researchers limit research to only discussing the challenges of the digital divide in the online learning process during the COVID-19 pandemic in Indonesia with research locations in three districts in West Java in 2020-2021. This research uses a qualitative approach, an exploratory paradigm, in a case study perspective. The data collection process was carried out under natural conditions in the form of observation, in-depth interviews and documentation studies. This study concludes that collaboration between government officials and the community has a positive impact on people's opportunities to carry out online learning processes during the COVID-19 pandemic. The challenges of the digital divide faced during the digital learning process can be partially overcome by collaboration between the government, the community and the private sector, although the approach taken is different at each research location.